2019
DOI: 10.1186/s13578-019-0329-4
|View full text |Cite
|
Sign up to set email alerts
|

DUSP8 phosphatase: structure, functions, expression regulation and the role in human diseases

Abstract: Dual-specificity phosphatases (DUSPs) are a subset of protein tyrosine phosphatases (PTPs), many of which dephosphorylate the residues of phosphor-serine/threonine and phosphor-tyrosine on mitogen-activated protein kinases (MAPKs), and hence are also referred to as MAPK phosphatases (MKPs). Homologue of Vaccinia virus H1 phosphatase gene clone 5 (HVH-5), also known as DUSP8, is a unique member of the DUSPs family of phosphatases. Accumulating evidence has shown that DUSP8 plays an important role in phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…In these pathways, BAMBI, WNT9A, SFRP1, PRKCB, SGK1, DUSP8, and DUSP6 were upregulated in the SWG group. BAMBI [58,59] and DUSP8 [60] can promote granulosa cell differentiation. These findings suggest that the differentiation ability of granulosa cells in the SWG ovarian stroma is better than that of the LG ovarian stroma at 730 days.…”
Section: Discussionmentioning
confidence: 99%
“…In these pathways, BAMBI, WNT9A, SFRP1, PRKCB, SGK1, DUSP8, and DUSP6 were upregulated in the SWG group. BAMBI [58,59] and DUSP8 [60] can promote granulosa cell differentiation. These findings suggest that the differentiation ability of granulosa cells in the SWG ovarian stroma is better than that of the LG ovarian stroma at 730 days.…”
Section: Discussionmentioning
confidence: 99%
“…The top 20 pathways (from the most significant, P < 10 −9 ) were shown in Fig. 2 C. Among these pathways, MAPK-ERK and calcium-cAMP signaling are believed as the master pathways regulating cell survival, antioxidants, antiapoptosis ( 36 , 37 ), energy metabolism, and lipid homeostasis ( 38 , 39 ). Previous report has showed that HG incubation, an in vitro model for study of NAFLD, induces lipid accumulation via increasing DNA promoter methylation signaling ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the relationship of promoter 5m CpG demethylation and gene expression from the results of KEGG pathway analysis, the expression of key genes ( DUSP7 , DUSP8 , and MAPK1 ) and their target genes cAMP response element-binding protein 5 ( CREB5 ), peroxiredoxin 6, and BCL2-associated agonist of cell death in the MAPK pathway, as well as the key genes CACNA1D (calcium voltage-gated channel subunit alpha1 D,), CACNA1A (calcium voltage-gated channel subunit alpha1 A), and CACNA1H (calcium voltage-gated channel subunit alpha1 H) (encoding for calcium voltage-gated channel subunits) and their targeting genes [ PGC1A , 3-hydroxy-3-methylglutaryl-coenzyme A reductase ( HMGR ), and FAS ] in the calcium-AMP-activated protein kinase ( AMPK ) pathway were determined by RT-PCR analysis. The DUSP-MAPK signaling pathway is the major pathway involved in cell survival/death and antioxidization ( 37 , 40 ), and the calcium signaling pathway controls lipid and energy metabolism ( 38 , 39 ). As expected, 25HC3S increased expression of DUSP8 by 5-fold and its targeting gene, CREB5 , by up to 20-fold, which is the key element involved in cell survival and death ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon activation via phosphorylation, MAPKs phosphorylate other protein kinases and transcription factors, including many inflammatory and apoptotic biomarkers. 28 Oxidative stress with increased ROS generation is a well-known inducer of MAPKs. It was reported that cadmium-mediated oxidative stress induced phosphorylation and activation of JNK and p38 MAPKs and subsequently enhanced the downstream inflammatory and apoptotic cascades.…”
Section: Discussionmentioning
confidence: 99%